The Short Textbook of Medical Laboratory for Technicians - Satish Gupte (Jaypee Brothers Medical Publishers, 2014)
An ideal laboratory technician is expected to be in possession of sound knowledge of procedures and test techniques. It is generally seen that sometimes many books are required for obtaining answers of simple and minor queries. Needless to say that techniques are discussed briefly and in a very simple and easy-to-understand language on microbiology, hematology, immunology, histopathology, blood transfusion, clinical pathology and clinical biochemistry. New materials like autoanalyzer, biological safety cabinet, Wood's lamp, enzyme-linked immunosorbent assay (Elisa), bone marrow aspiration/bone marrow biopsy, fine needle aspiration cytology (FNAC), disposal of waste products, etc. are added. All the chapters are thoroughly revised.